Edge-activated graphene nanopores for thermally robust hydrogen membrane separations - Chi Cheng; Lohyun Kim; Aaron H. Persad; Chun Man Chow; Rohit Karnik (Nature Communications)
Abstract Temperature-dependent, selective molecular diffusion through porous materials is crucial for membrane separations and is typically modeled as an Arrhenius-type activated process. Although this dependence can be described phenomenologically by an activation energy, tracing its molecular origins is often difficult, hindering robust membrane design for practical applications. Here, we investigate gas transport across monolayer nanoporous graphene membranes and observe significant, reversible, temperature-robust, and gas species-selective activated transport, with increased selectivity at rising temperatures, unlike many conventional membranes. Combined experiment and modelling trace this behavior to graphene nanopore edge functional groups, whose thermal fluctuations modulate effective pore size. This activated transport remains stable with aging over 1 year and shows selectivity exceeding 70 for hydrogen/hydrocarbon mixture separation at 220 °C, representative of dehydrogenation reactor temperatures. Our results demonstrate the thermal and long-term robustness of nanoporous graphene membranes, suggesting potential for precise engineering of nanopore surface chemistries in membranes for challenging molecular separations.